Suppressive effects of (-)-tubaic acid on RANKL-induced osteoclast differentiation and bone resorption. Issue 1 (11th December 2023) - Lim, Soomin; Ihn, Hye Jung; Kim, Ju Ang; Bae, Jong-Sup; Kim, Jung-Eun; Bae, Yong Chul; Shin, Hong-In; Kim, Tae Hoon; Park, Eui Kyun
ABSTRACT: Regulation of osteoclastogenesis and bone-resorbing activity can be an efficacious strategy for treating bone loss diseases because excessive osteoclastic bone resorption leads to the development of such diseases. Here, we investigated the role of (-)-tubaic acid, a thermal degradation product of rotenone, in osteoclast formation and function in an attempt to identify alternative natural compounds. (-)-Tubaic acid significantly inhibited receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclast differentiation at both the early and late stages, suggesting that (-)-tubaic acid affects the commitment and differentiation of osteoclast progenitors as well as the cell-cell fusion of mononuclear osteoclasts. (-)-Tubaic acid attenuated the activation of extracellular signal-regulated kinase (ERK) and expression of nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and its target genes in response to RANKL. Furthermore, a pit-formation assay revealed that (-)-tubaic acid significantly impaired the bone-resorbing activity of osteoclasts. Our results demonstrated that (-)-tubaic acid exhibits anti-osteoclastogenic and anti-resorptive effects, indicating its therapeutic potential in the management of osteoclast-related bone diseases.